Unconventional uranium in China's phosphate rock: Review and outlook - Shang, Delei; Geissler, Bernhard; Mew, Michael; Satalkina, Liliya; Zenk, Lukas; Tulsidas, Harikrishnan; Barker, Lee; El-Yahyaoui, Adil; Hussein, Ahmed; Taha, Mohamed; Zheng, Yanhua; Wang, Menglai; et al. (Renewable & sustainable energy reviews, 2021)
Some phosphate rock contains elevated concentrations of natural uranium. China is the largest phosphate rock producing country in the world and will soon have the largest uranium requirements in the world as well. Most phosphate rock deposits in China show low uranium concentrations (20–30 mg/kg) so that the recovery of radiotoxic heavy metals is neither economically appropriate nor ecologically necessary. China does, however, also have elevated uranium concentrations (≥90 mg/kg) in phosphate rock deposits in Sichuan and Yunnan. We estimate that China could have recovered nearly 648 metric tU (1.43 million lb U3O8) from those mines in 2016. The amount corresponds to 9.7% of the total reported uranium requirements in this year or 39.3% of reported domestic uranium production in 2016. The future uranium recovery potential may be even higher in total numbers (1158 tU or 3.01 million lb U3O8 in 2030). The main reason are potentially increasing imports of phosphate rock from large exporting countries such as Morocco that show higher average uranium content. In addition, medium- to lower-grade domestic phosphate rock resources with larger shares of accompanying heavy metals, that include rare earths and uranium, will have to be processed. Although the uranium supply for China is currently not at risk, the supply security could be further increased by obtaining unconventional uranium from domestic and imported phosphate rock. •We estimate the quantity of uranium that can be recovered from phosphates in China.•Uranium from phosphates could have covered 10% of China's uranium requirements in 2016.•Uranium from phosphates could be as high as 39% of the domestic production in 2016.•Future uranium recovery potential is even more considerable but dwarfed by uranium needs.•China may loosely follow a “four-fourths-rule” for the country's uranium supply security.